Application of Fast Fourier Transforms in Some Advanced Electroanalytical Methods - Norouzi, Parviz; Pirali-Hamedani, Morteza; Garakani, Tayebeh Mirzaei; Ganjali, Mohammad Reza (IntechOpen, 2011)
None